2023
DOI: 10.1101/2023.02.24.529954
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Variational Autoencoders for Generating Synthetic Tractography-Based Bundle Templates in a Low-Data Setting

Abstract: White matter tracts generated from whole brain tractography are often processed using automatic segmentation methods with standard atlases. Atlases are generated from hundreds of subjects, which becomes time-consuming to create and difficult to apply to all populations. In this study, we extended our prior work on using a deep generative model - Convolutional Variational Autoencoder - to map complex and data-intensive streamlines to a low-dimensional latent space given a limited sample size of 50 subjects from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
(52 reference statements)
0
2
0
Order By: Relevance
“…In addition, given the large number of streamlines and substantial proportion of false positives generated from tractography [14], modeling their joint distribution in a large cohort becomes challenging, but may potentially be tackled using deep learning methods. In our prior work [15], we showed that a convolutional variational autoencoder (ConvVAE) can embed tractography streamlines into a compact latent space and produce new bundles via generative sampling. Autoencoder-based architectures can also be used as a normative model (NM) [16], [17], where they encode statistical distributions of features from a healthy reference population.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, given the large number of streamlines and substantial proportion of false positives generated from tractography [14], modeling their joint distribution in a large cohort becomes challenging, but may potentially be tackled using deep learning methods. In our prior work [15], we showed that a convolutional variational autoencoder (ConvVAE) can embed tractography streamlines into a compact latent space and produce new bundles via generative sampling. Autoencoder-based architectures can also be used as a normative model (NM) [16], [17], where they encode statistical distributions of features from a healthy reference population.…”
Section: Introductionmentioning
confidence: 99%
“…Methods for synthetic data generation include explicitly creating samples with desired data distribution using computer graphics tools (e.g., in [2]) or algorithmically generating artificial data with the aid of special deep learning models (e.g., with techniques such as differential neural rendering [4], [5]. Neural style transfer [6], generative modeling techniques such as variational autoencoders (VAEs) [7] and generative adversarial networks (GANs) [8] have also been extensively used to generate synthetic data for training deep learning models. Another way to augment training data is by integrating existing data from several sources (e.g., in [9], [10], [11]).…”
mentioning
confidence: 99%